2012
DOI: 10.1089/ten.tea.2011.0479
|View full text |Cite
|
Sign up to set email alerts
|

Development of Microfabricated Dermal Epidermal Regenerative Matrices to Evaluate the Role of Cellular Microenvironments on Epidermal Morphogenesis

Abstract: Topographic features at the dermal-epidermal junction (DEJ) provide instructive cues critical for modulating keratinocyte functions and enhancing the overall architecture and organization of skin. This interdigitated interface conforms to a series of rete ridges and papillary projections on the dermis that provides three-dimensional (3D) cellular microenvironments as well as structural stability between the dermal and epidermal layers during mechanical loading. The dimensions of these cellular microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…μDERM fabrication was modified from a previous method [28] by incorporating fibroblasts into the dermal sponge and decreasing the thickness of the collagen gel-matrix (Figure 1). Specifically, a pattern was designed with a series of 200μm deep channels with varying widths (50μm, 100μm, 200μm, 400μm) [28, 29].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…μDERM fabrication was modified from a previous method [28] by incorporating fibroblasts into the dermal sponge and decreasing the thickness of the collagen gel-matrix (Figure 1). Specifically, a pattern was designed with a series of 200μm deep channels with varying widths (50μm, 100μm, 200μm, 400μm) [28, 29].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, a pattern was designed with a series of 200μm deep channels with varying widths (50μm, 100μm, 200μm, 400μm) [28, 29]. Type I acid-soluble collagen (10 mg/ml in 5 mM HCl) was purified from rat tail tendons [30, 31] and 0.3 ml of this collagen solution was self-assembled on the micropatterned molds using 5x DMEM (Invitrogen) with 0.22 M NaHCO 3 and 0.1 M NaOH (Sigma) for 18 hours at 37°C and 10% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pins et al developed microfabricated dermal-epidermal regeneration matrices comprised of 50 mm wide channels and showed that these synthetic 3D microenvironments may indeed create a protective environment for a regenerative population of keratinocytes similar to that of native skin tissue. 17,60 Based on these findings, the advantage of the Sharklet-micropatterned apical layer on the bilayered dressing evaluated here may be twofold: (1) accelerated epidermal cell migration and (2) guided development of appropriate keratinocyte niches at the dermal-epidermal junction.…”
Section: 59mentioning
confidence: 93%